Frequency of fetal blood sampling, delivery mode and neonatal outcome after revised CTG‐classification and updated lactate meter in Sweden: An observational study - Klara Gröndal; Erika Gyllencreutz; Stina Wretler; Kari Johansson; Malin Holzmann (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction A revised cardiotocography (CTG) classification was implemented in Sweden in 2017. Simultaneously, an updated version of the lactate meter, Lactate Pro 2™, proved to measure 50% higher than the previous, necessitating new cutoffs for fetal blood sampling (FBS). We aimed to investigate frequencies of FBS, delivery modes, and neonatal outcomes. We hypothesized that with the revised CTG classification, which accepts more fetal heart rate patterns as normal than the previous, the frequency of FBS would be lower, the proportion of acidemia at FBS and adverse neonatal outcomes would be higher among sampled fetuses, but not among the entire laboring population, and the higher lactate readings might increase the proportion of cesarean delivery in general anesthesia and cesarean delivery above vacuum extraction. Material and Methods A population‐based cohort study of electronic medical records of labors in Stockholm‐Gotland during 2014–2015 and 2018–2019, including singleton pregnancies >34 weeks, cephalic presentation, with spontaneous or induced start of labor. Outcome measures were FBS frequency, proportion of fetal acidemia, delivery modes, and neonatal outcomes with comparison between the two periods among sampled and nonsampled fetuses. Results There were 28 841 and 30 192 births during the two periods. In the latter period, the FBS frequency was lower (8.2% vs. 11.9% [p < 0.001]), and the proportion of acidemia at FBS was higher, both among sampled fetuses (12.5% vs. 7.1% [p < 0.001]), and in the total population (1.0% vs. 0.8% [p = 0.022]). Immediate cesareans in general anesthesia due to fetal distress were more frequent among sampled fetuses (3.1% vs. 2.0% [p = 0.006]) but not among nonsampled fetuses (0.4 vs. 0.4%). Incidence of Apgar scores < 4 at 5 min was unchanged after FBS (p = 0.66) but higher among nonsampled newborns (0.2 vs. 0.1 [p = 0.033]). Apgar scores <7 at 5 min were more frequent among both sampled and nonsampled groups. Conclusions After implementation of a revised CTG classification and a differently calibrated lactate meter in Sweden, the use of FBS was substantially lower. Acidemia at FBS and immediate cesarean due to fetal distress were more frequent among sampled fetuses but still low in the total laboring population. Low Apgar scores were more frequent among newborns both with and without FBS.